2015
DOI: 10.1007/s00477-015-1088-3
|View full text |Cite
|
Sign up to set email alerts
|

A supervised committee machine artificial intelligent for improving DRASTIC method to assess groundwater contamination risk: a case study from Tabriz plain aquifer, Iran

Abstract: Vulnerability maps are designed to show areas of greatest potential for groundwater contamination on the basis of hydrogeological conditions and human impacts. The objective of this research is (1) to assess the groundwater vulnerability using DRASTIC method and (2) to improve the DRASTIC method for evaluation of groundwater contamination risk using AI methods, such as ANN, SFL, MFL, NF and SCMAI approaches. This optimization method is illustrated using a case study. For this purpose, DRASTIC model is develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(29 citation statements)
references
References 62 publications
1
24
0
Order By: Relevance
“… normalDI=DrDw+RrRw+ArAw+SrSw1em+TrTw+IrIw+CrCw where r and w represent the rating and weight of layers, respectively, and the variables D , R , A , S , T , I , C correspond the seven parameters explained above. A high DRASTIC index (DI) value indicates high vulnerability (Barzegar et al ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… normalDI=DrDw+RrRw+ArAw+SrSw1em+TrTw+IrIw+CrCw where r and w represent the rating and weight of layers, respectively, and the variables D , R , A , S , T , I , C correspond the seven parameters explained above. A high DRASTIC index (DI) value indicates high vulnerability (Barzegar et al ).…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have used external parameters, such as land use and irrigation type and intensity, to improve the DRASTIC method (Secunda et al ; McLay et al ). Others have used the analytical hierarchy process (AHP), statistical methods, the Wilcoxon test, genetic algorithm (GA), and artificial intelligence (AI) (Panagopoulos et al ; Ahn et al ; Huan et al ; Barzegar et al ; Jafari and Nikoo ; Jang et al ; Kihumba et al ; Yang et al ) to overcome the limitations of the DRASTIC framework. In a study similar to the one presented here, Barzegar et al () used a multi‐model ensemble of machine learning algorithms in the Marand plain of northwest Iran to investigate vulnerability to contamination in multiple aquifers (e.g., unconfined, semiconfined, and confined).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation consists of red and green andesite tuff admixed with large quantities of blocks, boulders, gravel and sand of volcanic and alluvial origin with thickness of up to 500 meters and it has good quality groundwater resources (Barzegar et al 2015(Barzegar et al , 2016b.…”
Section: Geology and Hydrogeologymentioning
confidence: 99%
“…The presence of high nitrate concentration in the drinking water increases the incidence of gastric cancer and other potential hazards to infants and pregnant women (Nagireddi Srinivasa Rao 2006). Barzegar et al (2016b) studied the intrinsic vulnerability of Tabriz plain aquifer using the DRASTIC method. They indicated that the least vulnerable area was located in the west where the aquifer system is confined, while the most vulnerable areas were located in the east and south where the aquifer is unconfined and the recharge is high.…”
Section: Spatial Variability Of Groundwater Quality Parametersmentioning
confidence: 99%